Application of a wavelet transform for multispectral image fusion - Irina Borisova (Компьютерная оптика, 2020)
A method of image fusion based on wavelet decomposition of the original images is considered. An integrated monochrome image is formed from images of the same scene obtained in different spectral ranges. A strategy for fusing detail coefficients by comparing the proportions of their magnitudes for all original images is proposed. The fusion procedure does not require any thresholds. This fusion procedure can be performed for any number of original images. The algorithm does not introduce additional distortions and collects all the necessary information from the original images. The quantitative and qualitative evaluation of the results was performed. The proposed algorithm can be used in optoelectronic systems for automatic image processing.